Sudden Transition Between Classical to Quantum Decoherence in Bipartite Correlated Qutrit Systems - Retamal-Abarzua, J; Allende-Prieto, S; Cárdenas-López, F (Nature Publishing Group, 2017)
Classical to quantum decoherence transition, an issue existing for incoherent superposition of Bell-diagonal states is studied for three dimensional bipartite AB mixed quantum systems. Depending on the initial conditions, the dynamics of classical and quantum correlations can exhibit a sudden transition between classical to quantum decoherence. This result is calculated numerically by using entropic and geometric measures of correlations. An alternative explanation for this effect could be obtained by extending the bipartite A ⊗-B qutrit system to a pure tripartite A ⊗-B ⊗-C system. The freezing of classical correlations in AB is related to a freezing of the entanglement in the AC bipartition. © 2017 The Author(s).